Composite positive electrode lithium supplementing material and preparation method thereof, positive plate and secondary battery
By using composite positive electrode lithium supplement materials, combined with doped inorganic ternary compounds and organic lithium supplement agents, the problem of instability of existing positive electrode lithium supplement materials under high voltage systems has been solved, and higher energy density and Cycling performance and improve material stability in process workshop environment.
Patent Information
- Application Number
- CN202411370666.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The existing positive electrode lithium supplement material is unstable under the high-voltage lithium cobalt oxide system, resulting in capacity loss and energy density reduction, and is prone to failure in the process workshop.
A composite positive electrode lithium supplement material is used, which includes a core and a shell covered on the surface of the core. The core is a doped inorganic ternary compound and the shell is an organic lithium supplement agent, which is prepared by ball mill mixing and vacuum drying.
Improve the air stability of composite positive electrode lithium supplement material, block the contact between the material and humid air, reduce the first effect of lithium-rich lithium nickelate, provide more active lithium sources, improve the conductivity of the positive electrode sheet and the full battery energy density and high temperature cycling performance.
Smart Images

Figure BDA0005067491240000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a composite positive electrode lithium supplement material and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art
[0002] In the traditional consumer 3C electronics field, the most convenient way to pursue high volume energy density is to increase the overall voltage system of lithium cobalt oxide, thereby obtaining a high active lithium content. This puts higher requirements on the performance of lithium cobalt oxide positive electrode materials, such as energy density, and makes lithium cobalt oxide positive electrode materials also develop in the direction of high voltage. However, for the lithium cobalt oxide system, high voltage means that high delithiation state is equivalent to more unstable cobalt oxide. This leads to capacity loss and a decrease in energy density. In order to improve the energy density of lithium-ion batteries, many lithium compensation methods have been reported. According to the different compensation methods and locations, they can be roughly divided into the following three categories: (1) pre-embedded lithium by electrochemical method; (2) lithium compensation from the negative electrode; (3) lithium compensation from the positive electrode.
[0003] The current method of positive electrode lithium replenishment is to use positive electrode lithium replenishment additives in the positive electrode material system to improve the energy density and cycle life of the battery system. The mechanism of action of the positive electrode lithium replenishment additive is to decompose and release a large amount of lithium ions during the first week of charging, and reach the negative electrode through the electrolyte to make up for the loss of Li ions caused by the formation of the SEI film during battery formation. The excess lithium ions will also be stored in the negative electrode material and slowly released with the cycle to improve the battery's cycle performance. There are several representatives of positive electrode lithium replenishment active materials on the market: binary compounds Li 2 O, Li 2 O 2 , Li 3 N, etc., ternary compound Li 2 NiO 2 , Li 5 FeO 4 , Li 6 CoO 4 etc., and many organic compounds Li 2 C 2 O 4 , Li 2 C 3 O 5 , Li 2 C 4 O 4 Even though there are so many types of positive electrode lithium supplement materials, they are all limited by their own characteristics and cannot be fully used in high-voltage lithium cobalt oxide systems, such as extremely poor processing performance and high cost.
[0004] At present, mainstream material manufacturers use Li 2 NiO2 With Li 5 FeO 4 Mainly, these two main materials have extremely strict requirements on the process environment due to their strong water and carbon dioxide absorption properties. Inhaling more water and carbon dioxide in the process workshop will cause more residual lithium to be produced inside the electrode, and these residual lithium will often develop violent side reactions inside the entire battery system.
[0005] In view of this, it is indeed necessary to provide a technical solution to the above problems. Summary of the invention
[0006] One of the purposes of the present invention is to provide a composite positive electrode lithium replenishing material to address the deficiencies of the prior art, so as to improve the problem that the current positive electrode lithium replenishing active material absorbs water and carbon dioxide in the process workshop, resulting in instability of the positive electrode lithium replenishing active material, and to improve the energy density and cycle performance of the full battery.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A composite positive electrode lithium supplement material, the general chemical formula of which is Li x M y N (1-y) O z @Li a C b O c The composite positive electrode lithium supplement material comprises a core and a shell coated on the surface of the core;
[0009] Wherein, the core is a doped inorganic ternary compound, and its chemical formula is Li x M y N (1-y) O z , wherein M and N are selected from at least one of Ti, W, Ni, Cu, Zn, and Mg, respectively, 2≤x≤6, 0.1≤y≤0.5, and 2≤z≤6;
[0010] The shell is an organic lithium supplement, and its general chemical formula is Li a C b O c , wherein 2≤a≤4, 2≤b≤4, 2≤c≤4. Preferably, the organic lithium supplement comprises Li 2 C 2 O 4 , Li 2 C 3 O 5 , Li 2 C 4 O 4 At least one of them.
[0011] Preferably, the ratio of the mass of the shell to the total mass of the composite positive electrode lithium-supplementing material is 0.05% to 10%, and the mass ratio of the core to the shell is 1:0.1 to 0.3.
[0012] Preferably, the thickness D nm of the shell, the median particle size R1 μm of the shell material, the median particle size R2 μm of the core material and the pH value E of the core material satisfy the relationship: D-5≤10E*R1 / R2≤D+5.
[0013] Preferably, the thickness D of the shell is 45-55 nm, the median particle size R1 of the shell material is 1-5 μm, the median particle size R2 of the core material is 9-13 μm, and the pH value E of the core material is 10-12.
[0014] The second object of the present invention is to provide a method for preparing a composite positive electrode lithium supplement material, wherein the preparation environment is in an environment with a humidity of less than 2%, comprising the following steps:
[0015] S1, mixing a lithium source and a metal source; sieving the mixed material and pre-sintering it in an air environment, crushing and sieving it after natural cooling, and performing secondary sintering, and crushing and sieving it after natural cooling, and performing air flow pulverization to obtain a core material;
[0016] S2, heating and stirring the lithium source and the organic acid in an ethanol solvent, and drying to obtain a shell material;
[0017] S3. The core material and the shell material are ball-milled and mixed, and the obtained material is vacuum-dried to obtain a composite positive electrode lithium supplement material.
[0018] Preferably, in step S1, the molar ratio of the lithium source to the metal source is 2 to 6.8.
[0019] Preferably, the lithium source in steps S1 and S2 is at least one of lithium carbonate, lithium hydroxide, lithium oxide, and lithium nitrate, and the organic acid in step S2 is one of oxalic acid, oxalic acid, and squaric acid.
[0020] Preferably, in step S1, the pre-sintering temperature is 300-400°C, the heating rate is 5°C / min, and the insulation time is 5-7h; the secondary sintering is calcined under inert gas, the heating rate is 2°C / min, the sintering temperature is 700-800°C, and the insulation time is 13-16h.
[0021] The third object of the present invention is to provide a positive electrode sheet, comprising the composite positive electrode lithium supplement material described above.
[0022] A fourth object of the present invention is to provide a secondary battery comprising the positive electrode sheet described above.
[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: the composite positive electrode lithium replenishing material provided by the present invention comprises a core material and a shell material coated on the surface of the core material; the coating of the shell material can improve the air stability of the composite positive electrode lithium replenishing material, effectively prevent the material from contacting with humid air, and solve the problem that the current positive electrode lithium replenishing material is easily ineffective in the workshop environment; the core material is doped with metal elements, which can reduce the initial effect of lithium-rich nickel acid lithium, provide more active lithium sources, and the residual product of lithium-rich nickel acid lithium is metal oxide, which is beneficial to improve the conductivity of the positive electrode sheet; at the same time, the composite positive electrode lithium replenishing material does not gel when the slurry viscosity test is carried out under normal conditions, and the composite positive electrode lithium replenishing material has a high gram capacity and can effectively replenish the active lithium consumed by the negative electrode SEI film, thereby improving the energy density and high-temperature cycle performance of the whole battery. DETAILED DESCRIPTION
[0024] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.
[0025] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0026] In a first aspect of the present invention, a composite positive electrode lithium supplement material is provided, comprising a core and a shell coated on the surface of the core, and the chemical formula thereof is Li x M y N (1-y) O z @Li a C b O c The core is a doped inorganic ternary compound, the general chemical formula of which is Li x M y N (1-y) O z , wherein M and N are selected from at least one of Cu, Ti, Zn, Mg, and W, 2≤x≤6, 0.1≤y≤0.5, and 2≤z≤6; the shell is an organic lithium supplement, and its general chemical formula is Li a C b O c , where 2≤a≤4, 2≤b≤4, 2≤c≤4. The doped inorganic ternary compound Li x M y N (1-y) Oz It provides a large amount of irreversibly active lithium. The doping element does not affect the active lithium content of the core, while the metal oxides left after de-lithiation will reduce the organic lithium supplement Li x C y O z The decomposition potential can be completely decomposed at this potential, providing a small amount of active lithium, which is beneficial to improving the conductivity of the positive electrode sheet; therefore, the positive electrode lithium supplement material requires multiple steps of charging to completely release the active lithium.
[0027] In the shell, the organic positive electrode lithium supplement Li a C b O c The coating prolongs the time of failure of the positive electrode lithium supplement agent, and can solve the problem of side reactions of the positive electrode sheet in the process workshop under the conventional process environment. The composite lithium supplement material has a high gram capacity and a very low gel probability. Even after being mixed with the conventional positive electrode main material and rolled into a pole sheet, it has high hydrophobic and carbon dioxide repellent properties. At the same time, it can significantly improve the energy density and cycle performance after being assembled into a full battery with the conventional negative electrode main material.
[0028] In some embodiments, the organic lithium supplement includes Li 2 C 2 O 4 , Li 2 C 3 O 5 , Li 2 C 4 O 4 The organic lithium supplement can be in close contact with the metal oxide generated when the core material is completely separated. When charging continues, the decomposition potential of the organic lithium supplement decreases, and the decomposition can be completed within the normal operating voltage range of the lithium-ion secondary battery.
[0029] In some embodiments, the ratio of the shell mass to the total mass of the composite positive electrode lithium supplement material is 0.05% to 10%, specifically 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, which may include but are not limited to the values listed above; the mass ratio of the core material to the shell material is 1:0.1 to 0.3, specifically 1:0.1, 1:0.2, 1:0.3, which may include but are not limited to the values listed above, and is preferably 1:0.1.
[0030] In some embodiments, the thickness D nm of the shell, the median material particle size R1 μm of the shell, the median material particle size R2 μm of the core, and the material pH value E of the core satisfy the relationship: D-5≤10E*R1 / R2≤D+5.
[0031] In some embodiments, the thickness D of the shell is 45-55 nm, the median particle size R1 of the shell material is 1-5 μm, the median particle size R2 of the core material is 9-13 μm, and the pH value E of the core material is 10-12.
[0032] Among them, the thickness D of the shell material layer can be specifically 45nm, 50nm, 55nm, and can include but are not limited to the values listed above, preferably 50nm; the specific value of the median particle size R1 of the shell material can be 1μm, 2μm, 3μm, 4μm, 5μm, and can include but are not limited to the values listed above; the specific value of the median particle size R2 of the core material can be 9μm, 10μm, 11μm, 12μm, 13μm, and can include but are not limited to the values listed above; the pH value E of the core material can be specifically 10, 10.1, 10.2, 10.3, 10.4, 10.5, 10.6, 10.7, 10.8, 10.9, 11, 11.1, 11.2, 11.3, 11.4, 11.5, 11.6, 11.7, 11.8, 11.9, 12, and can include but are not limited to the values listed above.
[0033] A second aspect of the present invention provides a method for preparing the composite positive electrode lithium supplement material, wherein the preparation environment is in an environment with a humidity of less than 2%, comprising the following steps:
[0034] S1. Physically mix the lithium source and the metal source until the white color cannot be seen by naked eyes; sieve the mixed material and pre-sinter it in air environment, grind and sieve it after natural cooling, perform secondary sintering, grind and sieve it after natural cooling, and perform air flow grinding to obtain the core material;
[0035] S2, heating and stirring the lithium source and the organic acid in an ethanol solvent, and drying to obtain a shell material;
[0036] S3. Load the core material and the shell material into a ball mill, perform ball milling, and vacuum dry the obtained material to obtain a composite positive electrode lithium supplement material.
[0037] Among them, in step S1, the molar ratio of the lithium source to the metal source is 2 to 6.8. When preparing the core material, the lithium ratio is a key parameter. The M element is different, and the lithium ratio will be adjusted accordingly. When the M source is a nickel source, the lithium-nickel molar ratio is 2.03; when the M source is an iron source, the lithium-iron molar ratio is 5.3; when the M source is a cobalt source, the lithium-cobalt molar ratio is 6.5; thereby, a purer main material can be obtained, the gram capacity is increased, and the residual lithium will also increase accordingly, and the polarization degree of the material will increase.
[0038] In some embodiments, the lithium source in steps S1 and S2 is at least one of lithium carbonate, lithium hydroxide, lithium oxide, and lithium nitrate, and the organic acid in step S2 is one of oxalic acid, oxalic acid, and squaric acid.
[0039] In some embodiments, in step S1, the pre-sintering temperature is 300-400°C, the heating rate is 5°C / min, and the holding time is 5-7h; wherein the pre-sintering temperature can be 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C; it can include but is not limited to the values listed above, preferably 350°C; the holding time can be 5h, 6h, 7h, can include but is not limited to the values listed above, preferably 5h; the secondary sintering For calcination under inert gas, the heating rate is 3°C / min, the sintering temperature is 700-800°C, and the insulation time is 13-16h; wherein, the sintering temperature can be 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, and may include but are not limited to the values listed above, preferably 730°C; the insulation time can be 13h, 14h, 15h, 16h, and may include but are not limited to the values listed above, and is preferably 14h.
[0040] The third aspect of the present invention also provides a positive electrode sheet, comprising the composite positive electrode lithium supplement material described above, specifically comprising a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, and the positive electrode active material is the positive electrode material described in the present invention.
[0041] The positive electrode current collector can be any material suitable for use as a positive electrode current collector for lithium-ion batteries in the art. For example, the positive electrode current collector can include but is not limited to metal foil, and more specifically can include but is not limited to aluminum foil.
[0042] A fourth aspect of the present invention is to provide a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet described above.
[0043] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode active material layer may include but is not limited to one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium. Among them, the graphite can be selected from one or more of artificial graphite, natural graphite and modified graphite; the silicon-based material can be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; the tin-based material can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector is usually a structure or part that collects current. The negative electrode current collector can be various materials in the art that are suitable for use as a negative electrode current collector for lithium-ion batteries. For example, the negative electrode current collector can be, but is not limited to, metal foil, and more specifically, can be, but is not limited to, copper foil.
[0044] The separator can be any material suitable for lithium-ion battery separators in the art, for example, it can be a combination of one or more materials including but not limited to polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.
[0045] The secondary battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. The electrolyte lithium salt can be LiPF used in high temperature electrolytes. 6 and / or LiBOB; it can also be LiBF used in low temperature electrolytes 4 、LiBOB、LiPF 6 It can also be LiBF used in the overcharge-proof electrolyte 4 、LiBOB、LiPF 6 , LiTFSI; it can also be LiClO 4 、LiAsF 6 、LiCF 3 SO 3 、LiN(CF 3 SO 2 ) 2 At least one of the above. The organic solvent may be a cyclic carbonate, including PC, EC; it may also be a chain carbonate, including DFC, DMC, or EMC; it may also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to film-forming additives, conductive additives, flame retardant additives, overcharge prevention additives, and additives for controlling H in the electrolyte. 2 At least one of an additive for increasing the content of O and HF, an additive for improving low temperature performance, and a multifunctional additive.
[0046] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.
[0047] Example 1
[0048] The composite positive electrode lithium supplement material provided in this embodiment includes a core material and a shell material coated on the surface of the core material, wherein the chemical formula of the core material is Li 2 Ni 0.5 Cu 0.5 O 2 , the chemical formula of the shell material is Li 2 C 4 O 4 The chemical formula of the composite positive electrode lithium supplement material is Li 2 Ni 0.5 Cu 0.5 O 2 @Li 2 C 4 O 4 ;
[0049] Among them, the thickness D nm of the shell material layer is 50.99 nm, the median particle size R1μm of the shell material is 5μm, the median particle size R2μm of the core material is 11μm and the pH value E of the core material is 11.2, satisfying the relationship: D-5≤10E*R1 / R2≤D+5.
[0050] The preparation method of the composite positive electrode lithium supplement material is as follows:
[0051] Step 1: Physically mix lithium oxide, nickel oxide and copper oxide until the white color is not visible to the naked eye. The molar ratio of Li:Ni is 2.03, and the molar ratio of Ni:Cu is 5:5. The mixed materials are sieved through a 100-mesh sieve and placed in a pot. Pre-sintering is performed in a pit furnace in an air environment. The calcination program is set to 350°C for 5 hours, and the temperature rise rate is 5°C / min. After natural cooling, crush and sieve through a 100-mesh sieve, re-place in a pot, and place in a ventilated pit furnace. The calcination program is set to 730°C for 14 hours, and the temperature rise rate is 2°C / min. After natural cooling, crush through a 200-mesh sieve to obtain a core material with a D50 of 11μm, and the chemical formula is Li 2 Ni 0.5 Cu 0.5 O 2 , then seal and store;
[0052] Step 2: directly dissolve the squaric acid crystals and lithium nitrate in an ethanol solution, continue heating and stirring the squaric acid crystal solution, and slowly add the lithium nitrate solution after stirring for 5 minutes at 80°C; after the lithium nitrate solution is added, continue stirring for 30 minutes and then spray dry to obtain the shell material Li 2 C 4 O 4 ;
[0053] Step 3: weigh the core material and the shell material in a mass ratio of 1:0.1 and load them into a ball mill, adjust the speed to 400 RPM, and ball mill for 20 minutes; vacuum dry the obtained material at 120°C for 12 hours to obtain the composite positive electrode lithium supplement material Li 2 Ni 0.5 Cu 0.5 O 2 @Li 2 C 4 O 4 .
[0054] Preparation of positive electrode:
[0055] The composite positive electrode lithium supplement material in the above embodiment 1 and conventional lithium cobalt oxide are mixed with NMP in a ratio of lithium cobalt oxide: composite positive electrode lithium supplement material: conductive carbon: binder = 96.42:1.7:0.63:1.05 to form a positive electrode slurry, which is then vacuum stirred for degassing and then coated to form a positive electrode sheet.
[0056] Preparation of secondary batteries:
[0057] The above-mentioned positive electrode plate is assembled with a conventional 10% silicon-carbon negative electrode plate (i.e., the silicon content in the negative electrode material is 10% of the silicon-carbon mass), a high-voltage lithium supplement system electrolyte, and a separator into a secondary lithium-ion soft-pack battery. Except for the above-mentioned positive electrode plate, the remaining components can be purchased on the market.
[0058] Example 2
[0059] The difference between this embodiment and embodiment 1 is that the raw materials prepared in step 1 are lithium oxide, nickel oxide, and titanium oxide; the chemical formula of the core material obtained is Li 2 Ni 0.5 Ti 0.5 O 2 The composite positive electrode lithium supplement material obtained in step 3 is Li 2 Ni 0.5 Ti 0.5 O 2 @Li 2 C 4 O 4 ;
[0060] The rest is the same as in Example 1 and will not be described again here.
[0061] Example 3
[0062] The difference between this embodiment and embodiment 1 is that the raw materials prepared in step 1 are lithium oxide, nickel oxide, and zinc oxide; the chemical formula of the core material obtained is Li 2 Ni 0.5 Zn 0.5 O 2 The composite positive electrode lithium supplement material obtained in step 3 is Li 2 Ni 0.5 Zn 0.5 O 2 @Li 2 C 4 O 4 ;
[0063] The rest is the same as in Example 1 and will not be described again here.
[0064] Example 4
[0065] The difference between this embodiment and embodiment 1 is that the raw materials prepared in step 1 are lithium oxide, nickel oxide, and magnesium oxide; the chemical formula of the core material obtained is Li 2 Ni 0.5 Mg 0.5 O 2 The composite positive electrode lithium supplement material obtained in step 3 is Li 2 Ni 0.5 Mg 0.5 O 2 @Li 2 C 4 O 4 ;
[0066] The rest is the same as in Example 1 and will not be described again here.
[0067] Example 5
[0068] The difference between this embodiment and embodiment 1 is that the raw materials prepared in step 1 are lithium oxide, nickel oxide, and tungsten oxide; the chemical formula of the core material obtained is Li 2 Ni 0.5 W 0.5 O 2 The composite positive electrode lithium supplement material obtained in step 3 is Li 2 Ni 0.5 W 0.5 O 2 @Li 2 C 4 O 4 ;
[0069] The rest is the same as in Example 1 and will not be described again here.
[0070] Comparative Example 1
[0071] Lithium oxide and nickel oxide are physically mixed, and the rest of the synthesis method is the same as step 1 of Example 1 to obtain a positive electrode lithium supplement material with the chemical formula of Li 2 NiO 2 .
[0072] Comparative Example 2
[0073] The difference between this comparative example and Example 1 is that only step 1 is included, and step 2 and step 3 are not included, that is, the positive electrode lithium supplement material Li 2 Ni 0.5 Cu 0.5 O 2 ;
[0074] The rest is the same as in Example 1 and will not be described again here.
[0075] Comparative Example 3
[0076] The difference between this comparative example and Example 2 is that only step 1 is included, and step 2 and step 3 are not included, that is, the positive electrode lithium supplement material Li 2 Ni 0.5 Ti 0.5 O 2 .
[0077] The rest is the same as in Example 2 and will not be described again here.
[0078] Comparative Example 4
[0079] The difference between this comparative example and Example 3 is that only step 1 is included, and step 2 and step 3 are not included, that is, the positive electrode lithium supplement material Li 2 Ni 0.5 Zn 0.5 O 2 .
[0080] The rest is the same as in Example 3 and will not be described again here.
[0081] Comparative Example 5
[0082] The difference between this comparative example and Example 4 is that only step 1 is included, and step 2 and step 3 are not included, that is, the positive electrode lithium supplement material Li 2 Ni 0.5 Mg 0.5 O 2 .
[0083] The rest is the same as in Example 4 and will not be described again here.
[0084] Comparative Example 6
[0085] The difference between this comparative example and Example 5 is that only step 1 is included, and step 2 and step 3 are not included, that is, the positive electrode lithium supplement material Li2 Ni 0.5 W 0.5 O 2 .
[0086] The rest is the same as in Example 5 and will not be described again here.
[0087] Comparative Example 7
[0088] The positive electrode material in this comparative example adopts conventional lithium cobalt oxide material on the market, and is mixed with NMP in a ratio of lithium cobalt oxide: conductive carbon: binder = 98.12:0.63:1.05 to form a positive electrode slurry, which is then vacuum stirred for degassing and then coated to form a positive electrode sheet.
[0089] Comparative Example 8
[0090] The difference between this comparative example and Example 1 is that the D50 of the core material obtained in step 1 is 13 μm by using an inert gas to adjust the gas flow rate and the internal pressure of the air cavity through a jet mill.
[0091] The rest is the same as in Example 1 and will not be described again here.
[0092] Comparative Example 9
[0093] The difference between this comparative example and Example 1 is that in step 3, the mass ratio of the core material to the shell material is 1:0.5.
[0094] The rest is the same as in Example 1 and will not be described again here.
[0095] Comparative Example 10
[0096] The difference between this comparative example and Example 1 is that in step 3, the mass ratio of the core material to the shell material is 1:0.05.
[0097] The rest is the same as in Example 1 and will not be described again here.
[0098] The positive electrode materials and secondary batteries obtained in Examples 1-5 and Comparative Examples 1-10 were subjected to the following tests:
[0099] 1. Material property test: Mix the positive electrode lithium replenishing material with PVDF conductive carbon and NMP to observe its viscosity and gel state; mix the materials according to the formula of positive electrode lithium replenishing active material: conductive carbon: PVDF = 8:1:1, add an equal amount of NMP to each group, use a viscosity tester to test the viscosity, and observe its gel state with the naked eye.
[0100] No gel means the slurry can be stirred and processed normally;
[0101] Gel refers to the slurry that cannot be stirred normally after degassing, that is, it cannot be coated;
[0102] Slight gel means that the gel state of the prepared slurry is lighter after degassing.
[0103] 2. Lithium-ion secondary battery test: Calculate the volume energy density by measuring the thickness and power of the battery cell after the capacity division process.
[0104] The formula for calculating volume energy density is: capacity / cell volume;
[0105] The formula for calculating the capacity retention rate of 400 cycles of high temperature cycles is: 400th cycle high temperature cycle capacity / first cycle normal temperature cycle capacity, and the formula for calculating the expansion rate of 400 cycles of high temperature cycles is: 400th cycle battery cell PPG thickness measurement / first cycle normal temperature half-charged PPG thickness measurement. At the same time, the cycle retention rates of 400 weeks after adding different composite positive electrode lithium supplement materials are compared.
[0106] The test results of the above embodiments and comparative examples are summarized in Table 1.
[0107] Table 1
[0108]
[0109] As can be seen from the above table, compared with the uncoated comparative example, the composite positive electrode lithium replenishing active material provided by the present invention does not have the problem of physical / chemical gelation in a conventional humidity workshop, and compared with comparative examples 1-6, the slurry viscosity of the embodiment is lower, indicating that the coating layer can effectively isolate the moisture in the workshop, solve the current positive electrode lithium replenishing active material's characteristic of easily absorbing water and carbon dioxide, and improve practicality.
[0110] In addition, the composite positive electrode lithium supplement active material provided by the present invention improves the energy density of the lithium ion secondary battery. Compared with the comparative example 7 without lithium supplementation, or the comparative examples 1-6 without the shell, or the comparative example 8 that does not satisfy the relationship D-5≤10E*R1 / R2≤D+5, and the comparative examples 9-10 that do not satisfy the mass ratio of the core to the shell of 1:0.1-0.3, the embodiment has a significantly improved retention rate after 400 cycles of high temperature cycles, and a significantly reduced expansion rate of 400 cycles of high temperature cycles. This is very obvious for the improvement in the high silicon system, which is conducive to improving the cycle retention rate and improving the cycle expansion rate in the high silicon system and provides a clear direction.
[0111] In summary, the present invention provides a composite positive electrode lithium supplement material, the composite positive electrode lithium supplement material comprises a core and a shell coated on the surface of the core; the core is a doped inorganic ternary compound, and its chemical formula is Li x M y N (1-y) O z The shell is an organic lithium supplement, and its chemical formula is Li a C b O cAmong them, the coating of the shell can improve the air stability of the composite positive electrode lithium replenishing material, effectively block the contact between the material and humid air, and solve the problem that the current positive electrode lithium replenishing material is easy to fail in the workshop environment. The metal elements are doped in the core, which can reduce the initial effect of lithium-rich nickel acid lithium, provide more active lithium sources, and the residual product of lithium-rich nickel acid lithium is metal oxide, which is beneficial to improve the conductivity of the positive electrode sheet; the composite positive electrode lithium replenishing material synthesized by the present invention is subjected to the slurry viscosity test under normal environment without gelation. At the same time, the composite positive electrode lithium replenishing material has a high gram capacity and can effectively supplement the active lithium consumed by the negative electrode SEI film, thereby improving the energy density and high temperature cycle performance of the whole battery.
[0112] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A composite positive electrode lithium supplement material, characterized in that: Its chemical formula is Li x M y N (1-y) O z @Li a C b O c The composite positive electrode lithium supplement material comprises a core and a shell coated on the surface of the core material; Wherein, the core is a doped inorganic ternary compound, and its chemical formula is Li x M y N (1-y) O z , wherein M and N are selected from at least one of Ti, W, Ni, Cu, Zn, and Mg, respectively, 2≤x≤6, 0.1≤y≤0.5, and 2≤z≤6; The shell is an organic lithium supplement, and its general chemical formula is Li a C b O c , where 2≤a≤4, 2≤b≤4, 2≤c≤4.
2. A composite positive electrode lithium supplement material according to claim 1, characterized in that: The organic lithium supplement includes at least one of Li2C2O4, Li2C3O5, and Li2C4O4.
3. A composite positive electrode lithium supplement material according to claim 1, characterized in that: The ratio of the mass of the shell to the total mass of the composite positive electrode lithium supplement material is 0.05% to 10%, and the mass ratio of the core to the shell is 1:0.1 to 0.
3.
4. A composite positive electrode lithium supplement material according to claim 1, characterized in that: The thickness of the shell is Dnm, the median particle size of the shell material is R1μm, the median particle size of the core material is R2μm, and the pH value E of the core material satisfies the relationship: D-5≤10E*R1 / R2≤D+5.
5. A composite positive electrode lithium supplement material according to claim 4, characterized in that: The thickness D of the shell is 45-55 nm, the median particle size R1 of the shell material is 1-5 μm, the median particle size R2 of the core material is 9-13 μm, and the pH value E of the core material is 10-12.
6. A method for preparing a composite positive electrode lithium supplement material according to any one of claims 1 to 5, characterized in that: The preparation environment is in an environment with a humidity of less than 2%, including the following steps: S1, mixing a lithium source and a metal source; sieving the mixed material and pre-sintering it in an air environment, crushing and sieving it after natural cooling, and performing secondary sintering, and crushing and sieving it after natural cooling, and performing air flow pulverization to obtain a core material; S2, heating and stirring the lithium source and the organic acid in an ethanol solvent, and drying to obtain a shell material; S3. The core material and the shell material are ball-milled and mixed, and the obtained material is vacuum-dried to obtain a composite positive electrode lithium supplement material.
7. The method for preparing a composite positive electrode lithium supplement material according to claim 6, characterized in that: In step S1, the molar ratio of the lithium source to the metal source is 2 to 6.8; And / or, the lithium source in steps S1 and S2 is at least one of lithium carbonate, lithium hydroxide, lithium oxide, and lithium nitrate; And / or, the organic acid in step S2 is at least one of oxalic acid, oxalic acid, and squaric acid.
8. The method for preparing a composite positive electrode lithium supplement material according to claim 6, characterized in that: In step S1, the pre-sintering temperature is 300-400°C, the heating rate is 5°C / min, and the insulation time is 5-7h; the secondary sintering is calcined under inert gas, the heating rate is 2°C / min, the sintering temperature is 700-800°C, and the insulation time is 13-16h.
9. A positive electrode sheet, characterized in that: The composite positive electrode lithium supplement material comprises any one of claims 1 to 5.
10. A secondary battery, characterized in that: Including the positive electrode sheet as described in claim 9.
Citation Information
Patent Citations
Positive electrode lithium supplementing material, positive electrode plate containing positive electrode lithium supplementing material and electrochemical device
CN114175310A
Positive electrode lithium supplementing material and lithium ion battery comprising same
CN115498178A
Lithium supplement additive and preparation method and application thereof
CN115579474A
Composite lithium supplementing material and preparation method thereof, lithium supplementing coating and preparation method thereof, and lithium battery
CN116799210A
Positive electrode lithium supplementing material and preparation method and application thereof
CN117712328A